PENGARUH METODE RESITASI TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI BP KELAS X DI SMKN 14 BANDUNG - Hani Hadiati Pujawardani; Ervi Hervina (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This research is motivated by problems related to learning motivation in PAI BP subjects including, lack of focus during teaching and learning activities, students are not responsive or students are not active, lack of understanding of students in mastering the material provided. The objectives of this research are knowing the application of the Recitation Method on the subject of PAI BP class X at SMKN 14 Bandung, student learning motivation on PAI BP class X subjects at SMKN 14 Bandung, and the effect of the Recitation Method on students' learning motivation on the subject of PAI BP class X at SMKN 14 Bandung. This study uses a quantitative approach with descriptive analysis research methods. The total population in this study was 134 students and a sample of 40 students. The data analysis technique used is validity test, reliability test, parametric statistic prerequisite test, hypothesis test, and coefficient of determination test. Based on the results of the study, it can be seen that: the recitation method and student learning motivation, obtained an average value of 3.73 and 3.76, which are in the interval (3.41-4.20) including in the good category. Based on the data processing performed, the significance value of the recitation method in the coefficients table is 0.000, which is less than 0.05. It is concluded that Ho is rejected and H1 is accepted, which means that the recitation method has an effect on students' learning motivation. Based on the test results, the coefficient of determination has a correlation value of 0.331, the coefficient of determination is R20.109 which implies that the effect of the independent variable on the dependent variable is 10.9%.